Association of active γ-secretase complex with lipid rafts - Yasuomi Urano (Journal of Lipid Research, 2005)
Cholesterol has been implicated in the pathogenesis of Alzheimer's disease (AD). Although the underlying mechanisms are not yet clear, several studies have provided evidence for the involvement of cholesterol-rich lipid rafts in the production of amyloid β peptide (Aβ), the major component of amyloid deposits in AD. In this regard, the γ-secretase complex is responsible for the final cleavage event in the processing of β-amyloid precursor protein (βAPP), resulting in Aβ generation. The γ-secretase complex is a multiprotein complex composed of presenilin, nicastrin (NCT), APH-1, and PEN-2. Recent reports have suggested that γ-secretase activity is predominantly localized in lipid rafts, and presenilin and NCT have been reported to be localized in lipid rafts. In this study, various biochemical methods, including coimmunoprecipitation, in vitro γ-secretase assay, and methyl-β-cyclodextrin (MβCD) treatment, are employed to demonstrate that all four components of the active endogenous γ-secretase complex, including APH-1 and PEN-2, are associated with lipid rafts in human neuroblastoma cells (SH-SY5Y). Treatment with statins, 3-hydroxy-3-methylglutaryl-CoA-reductase inhibitors, significantly decreased the association of the γ-secretase complex with lipid rafts without affecting the distribution of flotillin-1. This effect was partially abrogated by the addition of geranylgeraniol.These results suggest that both cholesterol and protein isoprenylation influence the active γ-secretase complex association with lipid rafts.